THE INFLUENCE OF LIFESTYLE AND BRAND IMAGE ON REPURCHASE INTENTION OF NEW BALANCE SHOES IN PALU CITY: THE MEDIATING ROLE OF CUSTOMER SATISFACTION - Rejeki Tri Diva; Syamsul Bahri Dg. Parani; Ponirin; Mohammad Zeylo Auriza (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to examine the influence of lifestyle and brand image on repurchase intention with customer satisfaction as a mediating variable among New Balance shoe consumers in Palu City. Data were collected through a survey of 170 respondents who had purchased New Balance shoes, using a purposive sampling method. The analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The results showed that both lifestyle and brand image had a positive and significant effect on customer satisfaction and repurchase intention. In addition, customer satisfaction was proven to significantly mediate the relationship between lifestyle and brand image on repurchase intention. These findings reinforce the importance of managing brand image and tailoring products to consumer lifestyles to encourage customer satisfaction and loyalty, especially in the context of the Palu city market.